Analisis Kapasitas Sosial Ibu-Ibu Arisan Jabal Rahmah Setiabudi sebagai Penggerak Keluarga Bebas Stunting Berbasis Komunitas - Asra Dewita Namora Harahap; Rehan Mita Syaputri (Politeknik Kampar, 2025)
This study aims to describe the social capacity of Jabal Rahmah Setiabudi arisan women as a community-based stunting-free family mover. The approach used was descriptive quantitative, with a total of 30 respondents who were selected purposively. The instrument is a closed-ended questionnaire with a five-point Likert scale, covering five indicators of social capacity: participation in the community, knowledge about stunting, educational initiatives, community leadership, and collaboration with outsiders. The results of the analysis showed that the indicators of knowledge about stunting and participation in the community were in the high category, while educational initiatives were in the high and low category. The other two indicators, namely community leadership and collaboration with outside parties, are in the medium category. The average overall social capacity score is 3.52, including the high-low category. These findings show that the social capacity of arisan women is quite good and can be strengthened through community-based empowerment programs in a more targeted and sustainable manner.